Autoimmune Diseases of Digestive Organs-A Multidisciplinary Challenge: A Focus on Hepatopancreatobiliary Manifestation - Kunovsky, Lumir; Dite, Petr; Jabandziev, Petr; Kala, Zdenek; Vaculova, Jitka; Andrasina, Tomas; Hrunka, Matej; Bojkova, Martina; Trna, Jan (Journal of clinical medicine, 2021)
It is well known that some pathological conditions, especially of autoimmune etiology, are associated with the HLA (human leukocyte antigen) phenotype. Among these diseases, we include celiac disease, inflammatory bowel disease, autoimmune enteropathy, autoimmune hepatitis, primary sclerosing cholangitis and primary biliary cholangitis. Immunoglobulin G4-related diseases (IgG4-related diseases) constitute a second group of autoimmune gastrointestinal, hepatobiliary and pancreatic illnesses. IgG4-related diseases are systemic and rare autoimmune illnesses. They often are connected with chronic inflammation and fibrotic reaction that can occur in any organ of the body. The most typical feature of these diseases is a mononuclear infiltrate with IgG4-positive plasma cells and self-sustaining inflammatory response. In this review, we focus especially upon the hepatopancreatobiliary system, autoimmune pancreatitis and IgG4-related sclerosing cholangitis. The cooperation of the gastroenterologist, radiologist, surgeon and histopathologist is crucial for establishing correct diagnoses and appropriate treatment, especially in IgG4 hepatopancreatobiliary diseases.
Keywords: human leukocyte antigen; autoimmune hepatitis; inflammatory bowel disease; primary biliary cholangitis; primary sclerosing cholangitis; autoimmune pancreatitis; IgG4-related sclerosing cholangitis; IgG4-related hepatopathy; celiac disease